Ancient DNA Study in Medieval Europeans Shows an Association Between HLA-DRB1*03 and Paratyphoid Fever - Haller, Magdalena; Bonczarowska, Joanna H.; Rieger, Dirk; Lenz, Tobias L.; Nebel, Almut; Krause-Kyora, Ben (Frontiers in Immunology, 2021)
Outbreaks of infectious diseases repeatedly affected medieval Europe, leaving behind a large number of dead often inhumed in mass graves. Human remains interred in two burial pits from 14th century CE Germany exhibited molecular evidence of Salmonella enterica Paratyphi C (S. Paratyphi C) infection. The pathogen is responsible for paratyphoid fever, which was likely the cause of death for the buried individuals. This finding presented the unique opportunity to conduct a paratyphoid fever association study in a European population. We focused on HLA-DRB1*03:01 that is a known risk allele for enteric fever in present-day South Asians. We generated HLA profiles for 29 medieval S. Paratyphi C cases and 24 contemporaneous controls and compared these to a modern German population. The frequency of the risk allele was higher in the medieval cases (29.6 %) compared to the contemporaneous controls (13 %; p = 0.189), albeit not significantly so, possibly because of small sample sizes. Indeed, in comparison with the modern controls (N=39,689; 10.2 %; p = 0.005) the frequency difference became statistically significant. This comparison also suggested a slight decrease in the allele’s prevalence between the medieval and modern controls. Up to now, this is the first study on the genetic predisposition to Salmonella infection in Europeans and the only association analysis on paratyphoid fever C. Functional analysis using computational binding prediction between HLA variants and S. Paratyphi and S. Typhi peptides supported a reduced recognition capacity of bacterial proteins by DRB1*03:01 relative to other common DRB1 variants. This pattern could potentially explain the disease association. Our results suggest a slightly reduced predisposition to paratyphoid fever in modern Europeans. The causative allele, however, is still common today, which can be explained by a trade-off, as DRB1*03:01 is protective against infectious respiratory diseases such as severe respiratory syndrome (SARS). It is thus possible that the allele also provided resistance to corona-like viruses in the past.